169k views
4 votes
Solve the following equationX-3(x+2)=4 X - 3 ( x + 2 ) = 4

User Dodov
by
5.0k points

2 Answers

6 votes

Answer:

x = -5

Explanation:

Solve for 'x':

x - 3(x + 2)= 4

x - 3x - 3*2 = 4 {Distributive property}

x - 3x - 6 = 4

Combine like terms in LHS,

-2x - 6 = 4

Add 6 to both sides,

-2x = 4 + 6

-2x = 10

Divide both sides by (-2)

x = 10 ÷ (-2)


\sf \boxed{x= -5}

User Udit Kapahi
by
5.8k points
0 votes

Given: X-3(x+2)=4X-3(x+2)=4

Find: the solution of the given equation

Explanation:


\begin{gathered} X-3(x+2)=4 \\ X-3x-6=4 \\ X-3x=10......................(1) \\ 4X-3(x+2)=4 \\ 4X-3x-6=4 \\ 4X-3x=10...........................(2)\text{ } \end{gathered}

on solving equation (1) and (2) , we get

User Elsayed
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.